Financial knowledge and portfolio complexity in Singapore - KOH, Benedict S. K. (Institutional Knowledge at Singapore Management University, 2020)
Financial literacy in Singapore has not been analyzed in much detail, despite the fact that this is one of the world’s most rapidly aging nations. Using the Singapore Life Panel®, we explore older Singaporeans’ levels of financial knowledge and compare them to those observed in the United States. We assess portfolio complexity for these older households, to examine how financial literacy is related to outcomes of interest. We show that older Singaporeans’ levels of financial literacy are comparable overall to those in the United States, even though older Singaporeans score slightly lower on some dimensions (knowledge of interest and inflation), and slightly higher on their knowledge of risk diversification. We document that women are less informed than men about stock diversification, and educated people tend to be more financially knowledgeable than their less educated counterparts. We also find that financial literacy is positively associated with respondents having both more wealth and more diversified and complex portfolios.